2010
DOI: 10.1242/jcs.063834
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 9 signaling requires ERK1/2 activity in mouse granulosa and cumulus cells

Abstract: SummaryOvarian folliculogenesis is driven by the combined action of endocrine cues and paracrine factors. The oocyte secretes powerful mitogens, such as growth differentiation factor 9 (GDF9), that regulate granulosa cell proliferation, metabolism, steroidogenesis and differentiation. This study investigated the role of the epidermal growth factor receptor (EGFR)-extracellular signal-regulated kinase 1 and 2 (ERK1/2; also known as MAPK3/1) signaling pathway on GDF9 action on granulosa cells. Results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 61 publications
3
49
2
Order By: Relevance
“…Because GCs of Fshb −/− follicles contained detectable EGFR (although it was reduced compared with the heterozygotes), we tested whether EGFR signaling activity was impaired. MAPK3 and 1 are the principal effectors of EGFR signaling, and their activation by phosphorylation is necessary for cumulus expansion (21,28,39,50). Upon the addition of EGF, MAPK3/1 phosphorylation increased significantly in Fshb +/− follicles but did not change detectably in Fshb −/− follicles (Fig.…”
Section: Oocyte-secreted Factors Required For Egf Responses Are Functmentioning
confidence: 92%
See 1 more Smart Citation
“…Because GCs of Fshb −/− follicles contained detectable EGFR (although it was reduced compared with the heterozygotes), we tested whether EGFR signaling activity was impaired. MAPK3 and 1 are the principal effectors of EGFR signaling, and their activation by phosphorylation is necessary for cumulus expansion (21,28,39,50). Upon the addition of EGF, MAPK3/1 phosphorylation increased significantly in Fshb +/− follicles but did not change detectably in Fshb −/− follicles (Fig.…”
Section: Oocyte-secreted Factors Required For Egf Responses Are Functmentioning
confidence: 92%
“…Oocyte-secreted factors (OSFs), including growth differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15), are essential for EGF-induced Has2, Ptgs2, and Tnfaip6 up-regulation and cumulus expansion (46)(47)(48)(49)(50)(51). Their effects in GCs are transduced by activation of the Sma-and Mad-related proteins (SMAD) pathway.…”
Section: Oocyte-secreted Factors Required For Egf Responses Are Functmentioning
confidence: 99%
“…Su et al (2010) showed that oocytesecreted GDF9 and BMP15 and subsequent activation of SMAD2/3 in CCs is required for expression of the EGF receptor, which is a principle activator of ERK1/2 in CCs. Our studies elucidated the reciprocal relationship, by demonstrating that EGF receptor/ERK1/2 activity is required to maintain phosphorylation of the SMAD3 linker region, required for downstream SMAD2/3 signalling and oocyte-regulated granulosa/CC functions (Sasseville et al 2010). Together, these two studies suggest some form of feedback loop is operating in CCs between GDF9/BMP15-activated SMAD2/3 and EGF receptor/ERK1/2.…”
Section: Interactions Between Smad and Mapk Signallingmentioning
confidence: 92%
“…New evidence is emerging from mouse studies of requisite crosstalk between SMAD and MAPK signalling for coordinated oocyte-somatic cell development (Sasseville et al 2010, Su et al 2010. The role of p38 and ERK1/2 MAPK pathways in COC function in nonrodent species is limited, although some information is available for the pig.…”
Section: Participation Of Mapks In Porcine CC Expansion and Gene Exprmentioning
confidence: 99%
See 1 more Smart Citation